Basra Center for Hereditary Pediatric Blood Diseases, Patient Characteristics and Attitudes - Alhijaj, Basim A. A.; Tayeh, Farah H.; Almatooq, Hasnaa Atwan (International Journal of Innovative Research in Medical Science, 2024)
Background thalassemia and sickle cell diseases are highly prevent in our locality and in Basrah governorate, Basrah center for pediatric hereditary blood disease is one of biggest center in Iraq with large cohort of heterogenous patient groups registered, services, patient demography and attitudes all were preliminary expressed in this study in a descriptive way Method cross sectional descriptive study expressed general data and data from direct inquiry of selected sample regarding their QOL, satisfaction and complications Results Basrah center involve patient most of them are of SCD and thalassemia, sample selected showed that family breakage or social breakage was not evident in (79.5%).a general QOL scoring most of the studied sample specified fair score in (63.4%), ( 82.20%) were generally satisfied regarding their general health, 95.50% were showed collective fair and satisfied score in regard of acceptance of their general appearance, (27.7%) did agreed that physical pain is effecting their life,(24.1%) were dissatisfied regarding general health system while 58% showed collective of fair and satisfied score,(63.4%),(61.6 %) were satisfied regarding medical staff management were 34.8% showed dissatisfaction, accessibility to medical service was dissatisfied in (42.9 %) most of this response (79.7%) was from rural living candidates. This research conclusion Patient attitude regarding their life, disease impact and medical service are general good and recommend more interest is to be paid for the patient qualified medical services and social support and showed a limitation of being non comparative, descriptive approach need to be corresponded later with a more analytic data.